METHODS OF WORKING WITH PROVERBS AND SAYINGS IN FRENCH LANGUAGE LESSONS (Scientific journal of the Fergana State University, 2024)
This article is devoted to the problem of teaching French using proverbs and sayings in the educational process. Particular attention is paid to teaching a foreign language in secondary school. The author provides information about the technique of working with proverbs and proverbs in a foreign language lesson and their importance in teaching French. Proverbs and sayings serve to improve students' listening skills, pronunciation and rhythmic intonation, enrich their vocabulary, and develop speech abilities and skills. Through the use of proverbs and sayings, in addition to obtaining information about the customs, traditions and way of life of the country where the language is being studied, students' vocabulary and interest in science increases. In the process of teaching proverbs and sayings to students, it is very important to find an alternative to a proverb or saying given in a foreign language in their native language. By finding an alternative in their native language, students learn to compare. In the process of using proverbs and sayings, the teacher should create a positive atmosphere in the classroom so that students develop their vocabulary skills by engaging in free communication without facing any obstacles in learning proverbs and sayings.